THE UTILISATION OF THE CHILD SUPPORT GRANT BY CAREGIVERS: THE CASE OF BA-PHALABORWA MUNICIPALITY IN LIMPOPO PROVINCE - Khosa, Priscalia; Kaseke, Edwell (Social Work/Maatskaplike Werk, 2017)
The Child Support Grant (CSG) represents a major policy response to child poverty in South Africa. Based on qualitative research, the article explored how caregivers in Ba-Phalaborwa sub-district in the Limpopo province utilise the CSG. The findings revealed that the CSG is mostly utilised to buy food, clothes and school necessities for children. There were perceptions, though, that some recipients did not utilise the grant in the best interest of children. It is recommended that the Department of Social Development should monitor closely the utilisation of the grant to ensure that beneficiaries use the grant in the best interest of the children.